RATIONALIZATION OF ANTIBIOTIC USE PATTERNS IN UNDER-FREE PATIENTS WITH FEVER AND COUGH IN OUTPATIENT IN TUAN RONDAHAIM HOSPITAL, PEMATANG RAYA, SIMALUNGUN DISTRICT PERIOD JANUARY – MARCH - Dilla Sastia Mara; Muharti Sanjaya (PT. Radja Intercontinental Publishing, 2020)
Antibiotic drugs are intended to prevent and treat infectious diseases. Recently, however, experts and doctors have found that antibiotics are not as effective as they used to be. The frequency of using antibiotics that is high but not matched by appropriate or irrational provisions can have negative impacts, one of which can be resistance. This study aims to determine the rationalization of the pattern of antibiotic use in under-five patients at Tuan Rondahaim Hospital Pematang Raya, Simalungun Regency for the period January-March 2018 through retrospective data collection by means of secondary data collection. The research sample was 275 toddler patients. The results showed that the use of the most antibiotics was amoxicillin at 47.63%, the dose of antibiotics that met the rational category was 100%, and 0% irrational category. Antibiotic indications that show 100% rational categories, 0% irrational categories, length of use of antibiotics that meet 100% rational categories, 0% irrational categories.